KOMUNIKASI DALAM KEHIDUPAN BERAGAMA MELALUI BISINDO - I Made Sukma Muniksu (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
Living in a social and religious life, you will find very rapid differencesin communication between Deaf and Hearing Friends. So that eachindividual must respect and respect each other. In this way, religiousharmony will be realized. Listeners can learn BISINDO so they cancommunicate with Deaf Friends. Listening friends can learn starting fromthe easiest, namely recognizing letters and numbers. Because throughletters and numbers can provide symbols that are very useful incommunication. Communication is a basic human activity. There is not anindividual who will not be involved in communication. In this relationshipin communication, it is in the form of tolerance and information betweenreligious communities which are the core elements of limited religiousharmony within the internal environment of a religion. Meanwhile,horizontal relationships, or patterns of human relations with each other orhumans with surrounding communities of different cultures, races,religions, be it in the form of social cooperation or individual patterns withindividuals to build a stronger sense of brotherhood. A society with a socialand religious life definitely needs communication. Even though thecommunication occurred between Listening Friends and Deaf Friends. Allactivities that occur in religious life cannot be separated from thecommunication from the communicator to the communicant. A deaf friendwho uses BISINDO as a communicant has the right to know whatinformation he gets from other people. In a diverse life, Teman Deaf alsohas the right to receive religious teachings that he believes in.